2006
DOI: 10.1007/s00018-006-6600-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of fat metabolism in the liver: link to non-alcoholic hepatic steatosis and impact of physical exercise

Abstract: Hepatic steatosis may develop as a consequence of several dysfunctions. An increased circulating non-esterified fatty acid (NEFA) pool seems to be a major determinant in the pathogenesis of non-alcoholic fatty liver disease. Increased activation of the transcription factor sterol-regulatory-element-binding protein-1c, which promotes fatty acid synthesis, also contributes to hepatic fat accumulation. Increased hepatic fat oxidation with hepatic steatosis may be triggered by increased hepatic fat concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
97
1
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(106 citation statements)
references
References 193 publications
(225 reference statements)
1
97
1
7
Order By: Relevance
“…Taking into account the fact that excessive fatty liver accumulation appeared to be peculiarly associated with hepatic insulin resistance (5) and that reduction of the IHF content due to a moderate weight reduction was associated with improvement of hepatic insulin sensitivity (24), the potential beneficial effect of physical exercise would represent an additional tool to improve the metabolic profile of patients type 2 diabetes. The precise mechanisms by which physical exercise may reduce hepatic steatosis remains unknown and needs to be extensively explored, even if it was suggested that it would stimulate lipid oxidation and inhibit lipid synthesis in liver through the activation of the AMPactivated protein kinase pathway (25).…”
Section: Correlative Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Taking into account the fact that excessive fatty liver accumulation appeared to be peculiarly associated with hepatic insulin resistance (5) and that reduction of the IHF content due to a moderate weight reduction was associated with improvement of hepatic insulin sensitivity (24), the potential beneficial effect of physical exercise would represent an additional tool to improve the metabolic profile of patients type 2 diabetes. The precise mechanisms by which physical exercise may reduce hepatic steatosis remains unknown and needs to be extensively explored, even if it was suggested that it would stimulate lipid oxidation and inhibit lipid synthesis in liver through the activation of the AMPactivated protein kinase pathway (25).…”
Section: Correlative Analysismentioning
confidence: 99%
“…IHF content was assessed in a quantitative fashion and noninvasively as a continuous variable by means of 1 H magnetic resonance spectroscopy (MRS), and habitual physical activity was assessed by means of a questionnaire. Fatty liver was defined as IHF content of Ͼ5% wet weight, and insulin sensitivity was estimated using the computer homeostasis model assessment (HOMA)-2 indexes.RESULTS -A reduced prevalence of fatty liver in the quartile of the most physically active individuals (25,11,25, and 2% in quartile 1, 2, 3, and 4, respectively; 2 ϭ 15.63; P ϭ 0.001) was found along with an inverse correlation between the physical activity index and the IHF content when plotted as continuous variables (Pearson's r ϭ Ϫ0.27; P Ͻ 0.000). This association was not attenuated when adjusted for age, sex, BMI, HOMA-2, and adiponectin (partial correlation r ϭ Ϫ0.25; P Ͻ 0.001).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Decreased mitochondrial FA oxidation has long been considered as the primary mechanism underlying the disruptions in lipid metabolism in the liver leading to TG accumulation (36). Previously, reduced liver mRNA of PPARα and FA oxidizing enzymes, such as acyl-CoA oxidase, have been observed in several models of FA and/or insulin-resistant rodents (37).…”
Section: Articles Integrative Physiologymentioning
confidence: 99%
“…This occurs in part through the inhibition of SREBP1c by suppressing its gene transcription, mRNA stabilization and proteolytic cleavage in the liver (16). Given that plasma lipid concentration is directly related to the influx of lipids to the liver (36), defects in lipid oxidative capacity therefore further aggravate fat accumulation. Thus, it seems logical that decreased lipid synthesis reflects a compensatory mechanism in order to prevent further lipid accumulation.…”
Section: Articles Integrative Physiologymentioning
confidence: 99%